FRI0122 REAL-WORLD SAFETY DATA FROM PATIENTS WITH RHEUMATIC DISEASES TREATED WITH CT-P13, AN INFLIXIMAB BIOSIMILAR: AN INTERIM ANALYSIS FROM AN OBSERVATIONAL STUDY. (June 2019) - Taylor, Peter C.; Christensen, Robin; Moosavi, Shahrzad; Selema, Pamela; Guilatco, Ruffy; Fowler, Heather; Bombardier, Claire; Haraoui, Boulos
Abstract : Background: CT-P13, an infliximab biosimilar, has been available in Europe and Canada since 2015, and real-world experience with CT-P13 is important to support the safety of this medication. PERSIST is an ongoing, observational cohort study evaluating CT-P13 as treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) in a real-world setting. Objectives: This interim analysis reports safety outcomes for patients who received CT-P13 as their first biologic (Biologic-naïve) or who switched from infliximab reference product (IFX-RP) to CT-P13 (Switched) based on data collected from September 2015 to December 2017. Methods: Patients were recruited during usual care at 38 academic and community sites in 6 European countries and Canada. Adult RA, AS or PsA patients prescribed CT-P13 or locally-sourced IFX-RP at the investigator's discretion and according to the approved label were eligible. Data were analysed descriptively. Results: This analysis included 329 patients (RA, n=134; AS, n=110; PsA, n=85). Of these, 6 (1.8%) were not treated, 3 (0.9%) completed study treatment, 244 (74.2%) were ongoing and 76 (23.1%) discontinued study treatment, most commonly due to lack of response (30 [9.1%]). Demographics and baseline characteristics were generally similar between groups (Table 1 ). Most treatment-emergent adverse events (TEAEs; Table 2 ) were of mild or moderate intensity; 7/129 events were severe. Most commonly reported adverse events were related to infection (n=33; 10.2%); most frequently reported infection-related TEAEs were nasopharyngitis (n=6; 1.9%), respiratory tract infection (n=5; 1.5%) and pneumonia (n=4; 1.2%). No case of tuberculosis was reported. Eight (2.5%) patients reported infusion related reactions. Conclusion: Incidences of TEAEs were similar and there was no discernible pattern across the most common TEAEs between groups. These interim analysis results from the PERSIST study conducted in a real-world setting are consistent with the known safety profile of infliximab and do not demonstrate new safety information to change the benefit−risk profile of CT-P13. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc, Robin Christensen Grant/research support from: AbbVie Inc, and the Oak Foundation, Speakers bureau: Roche, Shahrzad Moosavi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Pamela Selema Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ruffy Guilatco Employee of: Pfizer Inc, Heather Fowler Consultant for: Pfizer UK Limited & Pfizer Inc, Claire Bombardier Grant/research support from: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Hospira, Janssen, Merck, Novartis, Pfizer Inc, Sanofi, Speakers bureau: Roche, Boulos Haraoui Grant/research support from: AbbVie Inc, Merck, and Novartis, Consultant for: AbbVie Inc, Amgen Inc, Eli Lilly, Novartis, Pfizer Inc, and UCB